Extra-pulmonary primary multidrug-resistant tubercular lymphadenitis in an HIV negative patient. (8th May 2012) - Kant, Surya; Saheer, S; Hassan, Ghulam; Parengal, Jabeed
Abstract : A 28-year-old woman without any history of prior antituberculosis treatment presented with cervical lymphadenopathy and a cold abscess near medial end of clavicle of 5 months duration. Pus culture and sensitivity revealed Mycobacterium tuberculosis resistant to rifampicin and isoniazid. Thus she was diagnosed as a case of primary multidrug-resistant tuberculosis and treated with second line drugs according to culture susceptibility pattern. On completion of therapy, patent showed good clinical response. This case highlights the observation that even extra-pulmonary primary multidrug-resistant tuberculosis can be successfully treated with currently available second line drugs.